Passing crisis and emergency risk communications: The effects of communication channel, information type, and repetition. (May 2015) - Edworthy, Judy; Hellier, Elizabeth; Newbold, Lex; Titchener, Kirsteen
Abstract: Three experiments explore several factors which influence information transmission when warning messages are passed from person to person. In Experiment 1, messages were passed down chains of participants using five different modes of communication. Written communication channels resulted in more accurate message transmission than verbal. In addition, some elements of the message endured further down the chain than others. Experiment 2 largely replicated these effects and also demonstrated that simple repetition of a message eliminated differences between written and spoken communication. In a final field experiment, chains of participants passed information however they wanted to, with the proviso that half of the chains could not use telephones. Here, the lack of ability to use a telephone did not affect accuracy, but did slow down the speed of transmission from the recipient of the message to the last person in the chain. Implications of the findings for crisis and emergency risk communication are discussed. Highlights: Written communication channels resulted in more accurate message transmission than spoken channels. Message repetition will increase the accuracy of message transmission, particularly for spoken messages. If people are free to choose how to communicate, they prefer to use the telephone. If people are unable to use the telephone, they prefer to communicate using email. Using the telephone speeds up communication but is less accurate.